Length- and age-based demographics of exploited populations of stout whiting, Sillago robusta Stead, 1908 - Gray, C.; Barnes, L.; Robbins, William; van der Meulen, D.; Ochwada-Doyle, F.; Kendall, B. (2017)
This study assessed variability in the length and age compositions, longevity, length-at-age and rates of growth and mortality of the east Australian stout whiting Sillago robusta Stead, 1908 population harvested by demersal trawl fisheries. Sampling was done over 2 years and was spatially stratified across three depth strata between 11 and 90 m at two locations approximately 400 km apart. There were no consistent depth-related differences in length and age compositions, but the mean and median length and age of the population was greater at the lower latitude location. Age classes 2 and 3 years dominated samples in the north, and 1 and 2 years in the south. Observed longevity was 10 years in the north, and 6 years in the south. Mean length-at-age was not consistently different between sexes, years or locations, nor did the von Bertalanffy growth function differ significantly between sexes, even though females had a greater estimated L 8 (23.45 cm FL) compared to males (22.36 cm FL). Estimated natural mortality (M) ranged between 0.42 and 0.77, using age- and length-based methods. Age-based catch-curve analyses identifie d the instantaneous rate of total mortality (Z) to range between 1.48 and 2.70, with subsequent estimates of fishing mortality (F) ranging between 1.15 and 2.00, being greater than M. Exploitation rates (E) were greater than 0.7, indicating that S. robusta at the study locations was heavily fished. The data provided here can be used as a basis to evaluate future fishery- and climate-related changes in the population demographics of east Australian S. robusta.